(untitled) - Beaumont, A. R. (Oxford, 2003)
Biotechnology and Genetics in Fisheries and Aquaculture is of great use to biological sciences students, particularly those studying marine, freshwater and aquatic biology, fish biology, fisheries, aquaculture, population biology and genetics. The book is also extremely useful as a reference to personnel such as fish farmers and fisheries scientists and all those working in fisheries and aquaculture management and research. Libraries in all universities and research establishments where biological sciences, fisheries and aquaculture are studied and taught should have copies of this book on their shelves.
Di truyền phân loại và quần thể,Di truyền quần thể thủy sinh vật,Di truyền thủy sản
Keywords: Fishes,Fishes; Molecular genetics,Breeding